Stability Study and a 14-Day Oral Dose Toxicity in Rats of Plantain Leaf Extract (Plantago lanceolata L.) Syrup - Mansoor, Kenza (Sci Pharm, 2017)
Plants have been used since antiquity to treat and prevent diseases. Plantain (Plantago lanceolata L.) is traditionally used for the treatment of the common cold and associated symptoms such as cough. This study was designed to evaluate the oral toxicity of plantain leaf extract-containing syrup. In preparation of the toxicological examination and to ensure the quality of the herbal preparation, analytical methods were developed and validated, and stability testing was performed. Physicochemical and microbial quality, thin layer chromatography patterns and high performance liquid chromatography fingerprints complied with the specifications during the entire period of stability testing. The marker substance, acteoside, remained within the stability-defining limits of 90%–110% for quantitative determinations. No hint of toxicity emerged from 14-day repeat dose toxicity testing in rats. The animals were given doses of 3, 6, or 12 mL of syrup per kg body weight by gavage twice daily. All animals showed normal appearance and behavior. Body and organ weights at the end of the study were similar to those in the control group. Overall, P. lanceolata syrup was found to be stable and non-toxic under the test conditions.